Contemporary Business Environment: Readings in Financial Accounting (Book). - Dominak, Geraldine F.; Pointer, Larry Gene (The Accounting Review, 1976)
Reviews the book "Contemporary Business Environment: Readings in Financial Accounting," by Levis D. McCullers and Relmond P. Van Daniker.